1979
DOI: 10.1080/15287397909529791
|View full text |Cite
|
Sign up to set email alerts
|

A newin vitromethod for testing plant metabolism in mutagenicity studies

Abstract: A rapid method was proposed to detect whether a harmless agricultural chemical can be converted into a mutagenic one by plant metabolism. The method is based on the use of Nicotiana alata cell cultures. Results obtained with five pesticides (atrazine, dichlorvos, tetrachlorvinphos, Kelevan, and maleic hydrazide) suggest that the proposed method simulates the metabolism of the whole plant. This procedure was also successfully applied to the genetic system of Aspergillus nidulans. One pesticide, atrazine, induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This positive response does not follow a direct doseresponse relationship and corroborates the fact that the herbicide is metabolized through P450 enzyme in vivo and in vitro in mammals by N-monodealkylation and isopropylhydroxilation (Adams et al 1990, Lang et al 1996, Hanioka et al 1999. In plants it has been shown that the triazine herbicide atrazine interferes with cell division producing chromosomal abnormalities (Liang and Liang 1972) and mutagenic and recombinogenic activity in Aspergillus nidulans (Benigni et al 1979, Kappas 1988. In Tradescantia 4430 clone stamen hair mutation the triazine herbicides triazene and simazine induced pink mutation events (Patussi and Bϋndchen 2013).…”
Section: Resultsmentioning
confidence: 55%
“…This positive response does not follow a direct doseresponse relationship and corroborates the fact that the herbicide is metabolized through P450 enzyme in vivo and in vitro in mammals by N-monodealkylation and isopropylhydroxilation (Adams et al 1990, Lang et al 1996, Hanioka et al 1999. In plants it has been shown that the triazine herbicide atrazine interferes with cell division producing chromosomal abnormalities (Liang and Liang 1972) and mutagenic and recombinogenic activity in Aspergillus nidulans (Benigni et al 1979, Kappas 1988. In Tradescantia 4430 clone stamen hair mutation the triazine herbicides triazene and simazine induced pink mutation events (Patussi and Bϋndchen 2013).…”
Section: Resultsmentioning
confidence: 55%
“…Preliminary results suggest that S-9 tissue preparations from rat liver did not activate maleic hydrazide into a mutagen whereas SI preparations from maize tissues activated this agent. However, Benigni et al (5) found that maleic hydrazide was not activated by N. alat~ell cultures. Recently SI preparations from wheat (Trit~aestivum) were found to activate pentac (pentachloro[2,4 cyclopentradiene]-yl) into a form weakly mUtagenic to S. typhimurium (Gentile, unpublished data).…”
Section: In Vitro Plant Activationmentioning
confidence: 96%
“…(1,4,5,6,7,8,8-heptachloro-3a,4,7,7a-tetrahydro-4,7-methanindene) were the only insecticides plant activated in the in vivo protocol.…”
Section: In Vivo Plant Activationmentioning
confidence: 99%
“…Our approach has been to incorporate cell-free extracts from various plant sources into the Salmonella assay plates. Similar attempts by others to evaluate plant metabolism have been relatively limited (Menn, 1978); Nicotiana cell cultures have been suggested as an activation system (Benigni et al, 1979), and corn (Plewa and Gentile, 1976;Gentile et al, 1977) or barley (Owais et a l . , 1978) seeds germinated in the presence of the test compound have been used to evaluate the mutagenicity of several pesticides.…”
mentioning
confidence: 95%